Low Testosterone Correlates with Delayed Development in Male Orangutans - Emery Thompson, Melissa (Public Library of Science, 2012)
Male orangutans (Pongo spp.) display an unusual characteristic for mammals in that some adult males advance quickly to full secondary sexual development while others can remain in an adolescent-like form for a decade or more past the age of sexual maturity. Remarkably little is understood about how and why differences in developmental timing occur. While fully-developed males are known to produce higher androgen levels than arrested males, the longer-term role of steroid hormones in male life history variation has not been examined. We examined variation in testosterone and cortisol production among 18 fully-developed (“flanged”) male orangutans in U.S. captive facilities. Our study revealed that while testosterone levels did not vary significantly according to current age, housing condition, and species origin, males that had undergone precocious development had higher testosterone levels than males that had experienced developmental arrest. While androgen variation had previously been viewed as a state-dependent characteristic of male developmental status, our study reveals that differences in the physiology of early and late developing males are detectable long past the developmental transition and may instead be trait-level characteristics associated with a male’s life history strategy. Further studies are needed to determine how early in life differences in testosterone levels emerge and what consequences this variation may have for male behavioral strategies.